Dynamics of Clay Particles in Non-vegetated Stormwater Biofilters - Daniel, N.S.; Logeswaran, T.; Tharshikka, V. (Springer, 2018)
Stormwater biofilters manage quantity and quality of urban stormwater runoff. Particulate solids from natural and anthropogenic sources accumulate on paved surfaces and eventually reach receiving waters. Retention of suspended solids in stormwater manage ment systems ensures the quality of stormwater runoff to water resources. Stormwater biofilters are similar in most of design parameters to sand filters employed in water treatment systems. The understanding and design of stormwater biofilters are often based on generic models of sand filters. Unlike water treatment sand filters, which are continuously fed, stormwater biofilters operate intermittently with spontaneously alternating wetting and drying cycles. This results in dynamic pol lutant removal pattern that employs different mecha nisms during and across rainfall events. As such, pilot scale biofilter columns fabricated with a layer of organic material were operated. Removal of suspended solids was very dynamic, where impact of age of filter, ante cedent dry days, and inflow quality varied during and across events. Flush of retained solids and filter material occurred during the stabilisation period during each event while very high removal percentages (more than 90%) were observed after stabilisation, during an event. Clogging was not observed due to re-entrainment, re distribution, and flush of retained solids during intermit tent wetting and drying cycles.
Keywords: Stormwater biofilters; Antecedent dry days; Turbidity; Total suspended solids; Clogging; Solids retention